On a method of legal knowledge base situational analysis - Paliulionienė, Laima (Lietuvos matematikos rinkinys, 2005)
Many existing knowledge base verification and validation methods can be applied to legal knowledge bases. However, peculiarities of legal knowledge raise the need for specific methods. Internal and external consistency of legal acts is a very important element of their quality. One of the consistency types is the consistency of quantitative values, for example, criminal and administrative sanctions (penalty size, duration of imprisonment, etc.), fees, grants, and pensions. This paper presents a method for the analysis of quantitative results of possible situations in order to detect inconsistencies in the results.
Keywords: legal knowledge bases; legimatics; verification and validation; knowledge base consistency